CORRELATION OF FIBROSCAN WITH GRADINGOF ESOPHAGEAL VARICES IN COMPENSATED ETHANOL, HBV, HCV AND NAFLD RELATED CIRRHOSIS - Velmurugan S, R Karthikeyan, B Sivasubramaniam, R Murali (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Esophageal varices (EV) are a major complication of cirrhosis, with grading influencingmanagement. This study evaluates the correlation between liver stiffness measurement(LSM) measured by FibroScan and EV severity in compensated ethanol, HBV, HCV and NAFLD related cirrhosis.